Rare Presentation of a Giant Paraspinal Chondrosarcoma: Case Report and Review of Literature - Vijayanarasimhan, Venkateshwaran; Sridhar, Krish (Asian Journal of Neurosurgery, 2025)
Chondrosarcomas are malignant chondrogenic neoplasms that primarily affect the bones of the pelvis and appendicular skeleton. Approximately 15% of these tumors occur in the chest wall. They most commonly originate anteriorly from the costochondral junction or sternum. Posterior thoracic chondrosarcomas frequently arise from the costal angle and vertebral arch of the thoracic spine, and only rarely do they originate at the costovertebral junction. A total of 30 patients with chondrosarcoma arising from the costovertebral junction have been previously reported in the English literature. We report a case of giant costovertebral chondrosarcoma presenting as a large paraspinal mass and review the current literature on the topic. A 42-year-old female with no comorbidities presented with a 3-month history of chest pain and dry cough. Radiologic imaging revealed a massive irregularly calcified paraspinal mass extending from the T5 to T7 vertebral levels. A microsurgical excision of the lesion was performed using a posterolateral thoracic approach, and intraoperatively, the mass was seen arising from the right T5 costovertebral junction with extension into the T4-T5 neural foramen. Histological examination confirmed a diagnosis of grade 2 chondrosarcoma. The uniqueness of our case report lies in the size and location of the chondrosarcoma, with only one other case being as large as ours. Chondrosarcoma must be considered in the differential diagnosis of partly calcified paraspinal masses arising from the costovertebral junction.
Keywords: chondrosarcoma; costovertebral; thoracic spine; paraspinal mass; posterolateral approach